American Finance Association, Report of the AFA Representative to the National Bureau of Economic Research - Hamada, Robert S. (Journal of Finance, 1995)
Robert S. Hamada, American Finance Association, Report of the AFA Representative to the National Bureau of Economic Research, The Journal of Finance, Vol. 50, No. 3, Papers and Proceedings Fifty-Fifth Annual Meeting, American Finance, Association, Washington, D.C., January 6-8, 1995 (Jul., 1995), pp. 1025-1027